2015
DOI: 10.1104/pp.15.01229
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced indeterminacy alters shade avoiding tomato leaf morphology

Abstract: Plants sense the foliar shade of competitors and alter their developmental programs through the shade-avoidance response. Internode and petiole elongation, and changes in overall leaf area and leaf mass per area, are the stereotypical architectural responses to foliar shade in the shoot. However, changes in leaf shape and complexity in response to shade remain incompletely, and qualitatively, described. Using a meta-analysis of more than 18,000 previously published leaflet outlines, we demonstrate that shade a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 66 publications
(109 reference statements)
1
49
0
Order By: Relevance
“…Thus, the timing of the types of leaves a plant displays is unaffected (Jones, 1995). This interpretation is also supported by recent work analyzing the transcriptomic responses in leaf primordia to simulated foliar shade and heteroblasty, showing that these phenomena in tomato leaf primordia are largely distinct at the molecular level (Chitwood et al, 2015a). Environmentally induced changes in leaf shape through timing-dependent (heterochronic) or timing-independent mechanisms are important, since field-based observations demonstrate that leaves plastically respond to their climate (Royer et al, 2009).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Thus, the timing of the types of leaves a plant displays is unaffected (Jones, 1995). This interpretation is also supported by recent work analyzing the transcriptomic responses in leaf primordia to simulated foliar shade and heteroblasty, showing that these phenomena in tomato leaf primordia are largely distinct at the molecular level (Chitwood et al, 2015a). Environmentally induced changes in leaf shape through timing-dependent (heterochronic) or timing-independent mechanisms are important, since field-based observations demonstrate that leaves plastically respond to their climate (Royer et al, 2009).…”
supporting
confidence: 57%
“…Environmentally induced changes in leaf shape through timing-dependent (heterochronic) or timing-independent mechanisms are important, since field-based observations demonstrate that leaves plastically respond to their climate (Royer et al, 2009). This plasticity often results in changes to marginal serrations and lobes that are morphological features explicitly modulated by heteroblastic pathways at the molecular level in the Brassicaceae (Rubio-Somoza et al, 2014), tomato (Solanum lycopersicum; Chitwood et al, 2015a), and Proteaceae (Ostria-Gallardo et al, 2015). Extant species distributions and the paleobotanical record attest to changes in these features during the evolution of flowering plants, especially long-lived woody perennials Sinnott, 1915, 1916;Webb, 1968;Wolfe, 1978Wolfe, , 1979Wolfe, , 1993Wolfe, , 1995Givnish, 1979Givnish, , 1984Hall and Swaine, 1981;Richards, 1996;Wilf, 1997;Wilf et al, 1998;Jacobs, 1999Jacobs, , 2002Feild et al, 2005;Traiser et al, 2005;Royer and Wilf, 2006;Peppe et al, 2011).…”
mentioning
confidence: 99%
“…6D). We previously showed that genes with high P1 transcript levels are enriched for photosynthetic-related GO terms compared to SAM/P0 genes enriched for transcription, cell division, and epigenetics-related GO terms (Chitwood et al, 2015), suggesting a genetic basis at both a functional and tissue-specific level for genes related to photosynthesis expressed preferentially in the P1 compared to the SAM/P0.…”
Section: Dissection Of Identified Eqtl To Spatially and Temporally Rementioning
confidence: 99%
“…We also analyzed hand dissected samples of the SAM + P0-P4 vs. the P5 collected over time (Fig. 6, B and C), representing genes regulated by vegetative phase change (heteroblasty; Chitwood et al, 2015).…”
Section: Dissection Of Identified Eqtl To Spatially and Temporally Rementioning
confidence: 99%
See 1 more Smart Citation